HEMATOPOIETIC STEM CELL SEPARATION FOR EXPERIMENTAL PURPOSES - METHODIC LIMITATIONS - Luzna, Pavla; Kylarova, Dana; Novak, Martin; Lichnovsky, Vaclav (Biomedical papers, 2009)
Background: Protooncogene CD117 is a cytokine receptor important for hematopoietic element development. Currently, we are not able to routinely separate a sufficient quantity of bone marrow CD117+ cells for experimental purposes.Aim: The aim of this study was to establish an immunomagnetic separation method for CD117+ hematopoietic stem cell isolation and to estimate the expression of chosen BCl-2 family protein members in these elements.Material and Methods: 120 samples of human and murine bone marrow were acquired using the magnetic separation system. The cells were stained for CD117, BCl-2, BAX, and CD33 by an indirect fluorescent immunocytochemistry.Results: The flow cytometry analysis showed only 2,6 % CD117+ cells from human as well as mouse bone marrow which is insufficient for further experiments. Cytospin was not good for morphologic characterization and immunophenotyping due to the fragility and destruction of the studied cells. Therefore, cell suspension staining was selected and by this method we found CD117 positivity in 70 % of the mononuclerar (CD33 positive) elements in the case of chronic myeloid leukaemia. Labelling of the BCl-2 family in this case showed antiapoptotic BCl-2 expression in 80 %, proapoptotic BAX expression in approximately 5 %.Conclusion: Our results show that CD117 immunomagnetic separation from bone marrow material is not acceptable for experimental purposes. They demonstrate that the only practical useful for the bone marrow cell examination (morphology and immunophenotype) is cell suspension staining which uncovers the distribution of both cytoplasmic proteins and surface antigens of immature blood elements.
Keywords: Stem cells/CD117/Immunomagnetic separation/Immunofluorescence